Performance evaluation methodology for gas turbine power plants using graph theory and combinatorics - Dev, Nikhil; Kumar, Raman; Saha, Rajeev Kumar; Babbar, Atul; Simic, Vladimir; Kumar, Raman; Bacanin, Nebojsa (International journal of hydrogen energy, 2024)
The design performance of real-time operating gas turbine power plants (GTPPs) deteriorates in terms of efficiency, reliability, and commercial availability due to aging, rubbing, contamination, and other similar problems. A manager minimizes operation and maintenance (O&M) expenses, consociating about the function of its basic structure (i.e., layout and design), availability (maintenance aspects), operation efficiency (trained workforce), safety and security, and other regulatory elements. Understanding plant structure improves performance, economical design, maintenance planning, etc. For a better understanding of design, a technique comprising graph theory, matrix method, and combinatorics is developed to determine the performance of GTPP. Detailed methodology for developing a system structure graph, various system structure matrices, and their permanent functions are described for the GTPP. For accessible and appropriate performance analysis, GTPP is divided into seven sub-systems. Structural interconnections between seven sub-systems of GTPP are as per real-time GTPP. The gas turbine system structure is developed in the form of a digraph. Matrix representation corresponding to digraph representation is developed, which is processed with the help of combinatorics. With the help of a computer programming tool developed in C++ for calculating the permanent of a matrix, the result comes out as a numerical value called the GTPP index. The methodology applied in the present work can be incorporated with standard computer programming tools developed for the performance assessment. In this way, it is easy to assess the dynamic behavior of the gas turbine system, as the methodology of the present work can incorporate tangible and intangible factors. Results obtained from the present methods agree with the available information in the literature. •The framework for exploring the dynamic behaviour of gas turbine systems is presented.•Graph theory, matrix method, and combinatorics are united into a single methodology.•Evaluations of efficiency, reliability, availability and maintainability are offered.•Recommendations for the ERAM evaluation of gas turbine systems are provided.